Success rates of probing for congenital nasolacrimal duct obstruction at various ages - Świerczyńska, Marta (BMC Ophthalmol, 2020)
BACKGROUND: Although nasolacrimal duct probing is the standard treatment for congenital nasolacrimal duct obstruction (CNLDO) among children, the optimal timing of this procedure has been a topic of debate. The aim of the study was to analyze the clinical efficacy of nasolacrimal duct probing among patients with CNLDO symptoms at various ages. METHODS: An 8-year retrospective study involved 2434 patients (3009 eyes), who underwent nasolacrimal duct probing conducted under topical anesthesia in the operating theatre. The study group consisted of 1148 girls (47.2%) and 1286 boys (52.8%) from 2 weeks to 41 months (average age was 8 ± 5.6 months). The participants were divided into nine age groups: 0–2 months, 3–6 months, 7–9 months, 10–12 months, 13–15 months, 16–18 months, 19–21 months, 22–24 months and over 24 months. RESULTS: Bilateral obstruction was present among 575 (23.6%) children and was associated with a higher percentage of unsuccessful procedures compared to patients with unilateral obstruction (16.9% vs 10.2%, p < 0.001 Chi-square test). The success rate of the initial probing was 87.2% for all children and it was shown that it decreased with age. In the above age groups, it was 87.9%; 91.4%; 89.6%; 86%; 76.3%; 71.3%; 70.3%; 70.2%; 65.4%, respectively. CONCLUSIONS: Probing is a safe and effective procedure. However, age at the time of the initial intervention and bilateral surgery constitute significant risk factors for failed probing. Probing between 7 and 9 months appears to be reasonable treatment strategy for children without recurrent infections. Early surgical intervention may be considered for patients with additional signs.